Lesbian health : current assessment and directions for the future - Solarz, Andrea L. (National Academy Press, 1999)
Women's health, as a field of study, is a developing discipline. Health theories in general have been based on studies of men. However, in recent years, more attention has shifted to women's health, realizing the disparities between men and women in relation to their health. During the last two decades, a similar shift has occurred for a group of women -- lesbian women -- to further identify and specify their health needs.